Current status of plant resources in the Ferghana Valley and opportunities to use them - M.R. Kholikulov (Universitas Muhammadiyah Sidoarjo, 2019)
In the southern part of Kurama mountains of North Fergana near Havasay, Chadaksay and Rezaksay on the relatively large areas of medicinal plants found Eremurus sogdiana, Perovskija scrophulariifolia and other species. And Ferula tenuisecta, Prangos pabularia, Ligularia alpigena, Lagotis korolkovii, Festuca valesiaca and others meet on the Angren plateau